Експортні можливості науково-технічного потенціалу оборонно-промислового комплексу України - Бріскін, А. З.; Шевченко-Марсель, В. І. (Видавництво Львівської політехніки, 2010)
Досліджені та проаналізовані стан і основні тенденції можливого розвитку зовнішньоекономічної діяльності України на базі використання науково-технічного потенціалу оборонно-промислового комплексу. In the article the state and main tendency of possible development Ukraines international active are researohed and analysed by usind the scientific technical potential of military industrial complex.
Export opportunities in scientific-technical potential of Ukrainian defense industry
Keywords: зовнішньоекономічна діяльність; науково-технічний потенціал; оборонний промисловий комплекс; sustainable development concept; economic development; environmental safety; the stages of policy implementation of sustainable environmental-economic development in EU countries; strategic goals